Preparation method of Lyocell fiber
By conducting multi-faceted performance evaluation and selecting products that meet standards for Lyocell fibers, the problem of fiber fibrillation tendency is solved, and performance improvement and application applicability are improved.
Patent Information
- Application Number
- CN202310948958.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
Lyocell fibers are prone to absorb water and expand in a wet environment, resulting in the destruction of hydrogen bonds between the fibres, weakening of the lateral binding force, and then separation and fibrillation under the action of external mechanical forces, limiting its application in textiles.
By evaluating the prepared Lyocell fibers in multiple aspects of cross-linking performance, mechanical properties, long-term performance and application performance, the fiber products that meet the standards are selected to ensure that they are met in multiple performance indicators, thereby reducing the tendency of fibrillation.
It has achieved the improvement of Lyocell fiber in multiple properties, meeting the requirements of cross-linking performance, mechanical performance, long-term performance and application performance, reducing fibrillation phenomenon, and improving the stability and application applicability of the fiber.
Smart Images

Figure BDA0004367547850000131 
Figure BDA0004367547850000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber preparation, and in particular to a method for preparing Lyocell fiber. Background Art
[0002] Lyocell fiber is a cellulose fiber produced by dry-jet wet spinning with N-methylmorpholine-N-oxide (NMMO) as solvent. Lyocell fiber uses wood pulp, bamboo pulp and cotton pulp as raw materials. During the preparation process, the recovery rate of NMMO reaches more than 99.5%, which is economical and applicable. The production process is green and environmentally friendly and pollution-free.
[0003] Lyocell fibers have high crystallinity and orientation. They easily absorb water and swell in a wet environment, which destroys the hydrogen bonds between the fibrils and weakens the lateral bonding force. Therefore, under the action of external mechanical forces, the fibrils will separate from each other, peeling off the fiber surface and causing fibrillation. The fibrillation tendency of Lyocell fibers causes pilling in textiles during washing, which seriously limits the application of Lyocell fibers. Summary of the invention
[0004] In view of this, the present invention provides a method for preparing Lyocell fiber, which can be evaluated from four aspects: cross-linking performance, mechanical properties, long-cycle performance and application performance, so that the finished Lyocell fiber meets the performance requirements in these four aspects and is more suitable for practical use.
[0005] In order to achieve the above first object, the technical scheme of the preparation method of Lyocell fiber provided by the present invention is as follows:
[0006] The preparation method of Lyocell fiber provided by the present invention comprises the following steps:
[0007] Performing performance evaluation on the prepared Lyocell fiber, the performance evaluation including: cross-linking performance evaluation, mechanical performance evaluation, long-cycle performance evaluation, and application performance evaluation, to obtain evaluation results;
[0008] According to the evaluation results, Lyocell fibers that meet the evaluation standards are selected to obtain Lyocell fiber products.
[0009] The preparation method of Lyocell fiber provided by the present invention can also be further implemented by adopting the following technical measures.
[0010] Preferably, the cross-linking performance evaluation index includes one or more of the following: the reaction amount of the cross-linking agent, the change of the fiber wet wear value over time, the wet wear value and coefficient of variation of the fiber after adding alkali and heating, the halogen content on the fiber, and the number of times the fiber can resist beating.
[0011] Preferably, the long-term performance evaluation index includes the reaction degree of fiber pH, fiber wet abrasion value, Halle factors F1 and F2 with aging time and / or shelf life.
[0012] Preferably, the mechanical property evaluation indexes include fiber Haller factors F1 and F2.
[0013] Preferably, the application performance evaluation index includes one or more of fiber spinning performance, fiber anti-beating times, and fiber dust amount.
[0014] Preferably, the method for detecting the reaction amount of the cross-linking agent comprises the following steps:
[0015] Get the name of the crosslinking agent used in the preparation of Lyocell fibers;
[0016] According to the name of the cross-linking agent, determine the characterizing element of the cross-linking agent, wherein the characterizing element of the cross-linking agent is an element contained in the cross-linking agent but not contained in the Lyocell fiber;
[0017] Detecting the content difference of the characterizing element in the crosslinking agent before and after the Lyocell fiber is prepared, and obtaining the reaction amount of the crosslinking agent through conversion;
[0018] Wherein, the characterizing elements of the cross-linking agent are tested by an organic element analyzer.
[0019] Preferably, the method for detecting the change of fiber wet wear value over time comprises the following steps:
[0020] Under the set conditions, different detection moments are selected within the set time interval;
[0021] At different testing moments, the wet wear value of the tested fiber is tested respectively;
[0022] The detection time is taken as the horizontal coordinate, and the wet wear value of the fiber to be detected corresponding to the detection time is taken as the vertical coordinate, so as to obtain the change of the fiber wet wear value over time.
[0023] Preferably, the set conditions include a temperature range of -20°C to 100°C and a humidity range of 0-100%.
[0024] Preferably, the method for detecting the wet wear value and coefficient of variation of the fiber after adding alkali and heating comprises:
[0025] The preliminarily prepared fiber to be tested is subjected to an alkali solution of a set concentration, and is heated for a set time under a set temperature condition to obtain the fiber to be tested after adding alkali and heating;
[0026] After the alkali-added and heated fiber to be tested is washed and dried, the wet abrasion value and coefficient of variation of the fiber after alkali-added and heated are calculated based on the washed and dried fiber to be tested and the initially prepared fiber to be tested.
[0027] Preferably, in the step of detecting the wet abrasion value and the coefficient of variation of the fiber to be tested after adding alkali and heating,
[0028] The alkali solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate;
[0029] In the alkali solution, the mass percentage of the solute is 0.5%-5%;
[0030] The amount of lye used is 5 to 100 times the mass of the fiber to be tested;
[0031] The set temperature range of alkali solution treatment is 0℃-100℃, and the set time range of alkali solution heating treatment is 10s-60min;
[0032] The drying temperature of the fiber to be tested after adding alkali and heating is in the range of 50°C-100°C, and the drying time is in the range of 30s-60min.
[0033] Preferably, the method for detecting the halogen content on the fiber comprises the following steps:
[0034] Using a digestion solution under a digestion condition to digest the fiber to be tested, to obtain the digested fiber to be tested;
[0035] The halogen content in the fiber to be tested after the digestion is detected to obtain the halogen content on the fiber.
[0036] Preferably, during the digestion step,
[0037] The digestion solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, sulfuric acid, and nitric acid;
[0038] The digestion temperature ranges from 90°C to 300°C, the digestion time ranges from 1h to 24h, the mass percentage of the solute in the digestion solution ranges from 0.1% to 10%, and the mass of the digestion solution used is 5 to 100 times the mass of the fiber to be tested.
[0039] Preferably, in the performance index of fiber pH change with aging time, the method for detecting fiber pH comprises the following steps:
[0040] Place 1g-10g of the fiber to be tested in a container;
[0041] Adding desalted water in an amount of 5 to 15 times the mass of the fiber to be tested into the container, so that the fiber to be tested is fully in contact with the desalted water, to obtain a mixture of the fiber to be tested and the desalted water;
[0042] The container is sealed, so that the mixture of the fiber to be tested and the desalted water is placed at room temperature for 1-24 hours to obtain the fiber to be tested after placement;
[0043] Squeeze out excess water from the fiber to be tested after being placed to obtain a sample of the fiber to be tested;
[0044] Detection to obtain the pH of the sample to be tested.
[0045] Preferably, the shelf life is the time interval from the completion of preparation of the fiber to be tested to the failure of the fiber to be tested, wherein the failure of the fiber to be tested is when the final wet wear number of the fiber to be tested is less than 200 times. At this time, the fiber to be tested no longer has anti-fibrillation performance, and the wet wear number is tested using the FZT 52019-2018 standard.
[0046] Preferably, the calculation formulas for the Haller factors F1 and F2 of the tested fiber are:
[0047] F1=-1.109+0.03992×FFk-0.06502×FDk+0.04634×FFn-0.04048×FDn+0.08936×NM+0.02748×SFk+0.025595KFk
[0048] F2=-7.070+0.02771×FFk+0.04335×FDk+0.02541×FFn+0.03885×FDn-0.01542×NM+0.2891×SFk+0.1640×KFk
[0049] In the formula,
[0050] FFk-dry breaking strength of the tested fiber after moisture conditioning (cN / tex),
[0051] FDk-dry breaking elongation of the tested fiber after moisture conditioning (%),
[0052] FFn-wet breaking strength of the fiber to be tested (cN / tex),
[0053] FDn-wet breaking elongation of the tested fiber (%),
[0054] NM-wet modulus of the tested fiber at 5% elongation (cN / tex / 5%),
[0055] SFk-Hook dry strength of the tested fiber after moisture conditioning (cN / tex),
[0056] KFk-knot strength of the tested fiber after moisture conditioning (cN / tex),
[0057] Parameters FFk, FDk, FFn, FDn, NM, SFk, and KFk all adopt GB / T 14337-2008 standard.
[0058] Among them, the Haller factor F1 of the common type of Lyocell fiber to be tested is 2-3, and F2 is 2-8.
[0059] Preferably, the fiber spinning performance includes one or more of the yarn strength, +140% cotton neps, and +200% cotton neps of the tested fiber sample after spinning.
[0060] Preferably, the method for detecting the fiber anti-flapping times comprises the following steps:
[0061] Take 0.01g-1g of the fiber to be tested;
[0062] Adding deionized water in an amount equivalent to 100 to 1200 times the mass of the fiber to be tested to the fiber to be tested, to obtain a mixture of the fiber to be tested and the deionized water;
[0063] Placing a mixture of the fiber to be tested and deionized water in a test bag to obtain a test bag containing the sample to be tested;
[0064] The test bag containing the sample to be tested is subjected to a beating test in a beating instrument, wherein the beating frequency of the beating instrument is set to 5 times / s-20 times / s;
[0065] The occurrence of fibrillation in more than 10% of the fibers in the sample to be tested is taken as the detection termination index, and the corresponding number of beatings at this time is taken as the number of fiber anti-beatings.
[0066] Preferably, during the step of taking the occurrence of fibrillation in more than 10% of the fibers in the sample to be tested as the detection termination indicator and taking the corresponding number of flapping times at this time as the number of fiber anti-flapping times, the sample to be tested is observed through an optical microscope.
[0067] Preferably, the method for detecting the amount of fiber dust comprises the following steps:
[0068] Obtaining all solutions in the cross-linking process of the fiber to be tested, wherein the cross-linking process refers to the entire process from applying the cross-linking additive to cleaning the fiber;
[0069] filtering the solution to obtain a filter residue;
[0070] The filter residue is dried and weighed to obtain the fiber dust amount.
[0071] The preparation method of Lyocell fiber provided by the present invention can be evaluated from four aspects: cross-linking performance, mechanical properties, long-cycle performance and application performance, so that the obtained finished Lyocell fiber meets the performance requirements of these four aspects, and, based on the conclusions obtained from the evaluation, the quality of the prepared Lyocell fiber can be evaluated, thereby providing a more comprehensive reference for purchasers. DETAILED DESCRIPTION
[0072] In view of this, the present invention provides a method for preparing Lyocell fiber, which can be evaluated from four aspects: cross-linking performance, mechanical properties, long-cycle performance and application performance, so that the finished Lyocell fiber meets the performance requirements in these four aspects and is more suitable for practical use.
[0073] After arduous efforts, the inventor discovered that
[0074] Many researchers have done a lot of research in this area, trying to find ways to reduce its fibrillation tendency. Among them, the products that have been successfully marketed are Lenzing's Lyocell LF and Tencel A100 cross-linked fibers. The cross-linking agent used in Lyocell LF cross-linked fiber is 2,4-dichloro-6-hydroxy-1,3,5-triazine sodium salt (NHDT), and the cross-linking agent used in Tencel A100 cross-linked fiber is 1,3,5-triacryloylhexahydro-1,3,5-triazine (TAHT). The evaluation of cross-linked fibers only stays on the cross-linking performance, and the essential differences of cross-linked fibers prepared by different cross-linking agents are not reflected.
[0075] However, there are currently few performance index evaluation methods established for cross-linked fibers. Therefore, it is impossible to judge the quality of the finished product of cross-linked Lyocell fibers by performance indicators.
[0076] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a Lyocell fiber preparation method proposed by the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiment. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0077] The term "and / or" in this article is merely a description of the association relationship of associated objects, indicating that three relationships may exist, for example, A and / or B. Specifically, it is understood that: A and B may be included at the same time, A may exist alone, or B may exist alone, and any of the above three situations may be met.
[0078] The preparation method of Lyocell fiber provided by the present invention comprises the following steps:
[0079] Step S1: performing performance evaluation on the prepared Lyocell fiber, the performance evaluation including: cross-linking performance evaluation, mechanical performance evaluation, long-cycle performance evaluation, and application performance evaluation, and obtaining evaluation results;
[0080] Step S2: According to the evaluation results, select Lyocell fibers that meet the evaluation standards to obtain Lyocell fiber products.
[0081] The preparation method of Lyocell fiber provided by the present invention can be evaluated from four aspects: cross-linking performance, mechanical properties, long-cycle performance and application performance, so that the obtained finished Lyocell fiber meets the performance requirements of these four aspects, and, based on the conclusions obtained from the evaluation, the quality of the prepared Lyocell fiber can be evaluated, thereby providing a more comprehensive reference for purchasers.
[0082] Among them, in step S1, the cross-linking performance evaluation index includes one or more of the following: the reaction amount of the cross-linking agent, the change of the fiber wet wear value over time, the wet wear value and coefficient of variation of the fiber after adding alkali and heating, the halogen content on the fiber, and the number of times the fiber can resist beating.
[0083] Wherein, in step S1, the long-term performance evaluation index includes the reaction degree of fiber pH, fiber wet abrasion value, and Haller factors F1 and F2 with aging time and / or shelf life.
[0084] Wherein, in step S1, the mechanical property evaluation index includes fiber Haller factors F1 and F2.
[0085] Wherein, in step S1, the application performance evaluation index includes one or more of the fiber spinning performance, the fiber anti-beating times, and the fiber dust amount.
[0086] Wherein, in step S1, the method for detecting the reaction amount of the cross-linking agent comprises the following steps:
[0087] Step S101: obtaining the name of the cross-linking agent in the preparation process of Lyocell fiber;
[0088] Step S102: Determine the characterizing element of the crosslinking agent according to the name of the crosslinking agent, wherein the characterizing element of the crosslinking agent is an element contained in the crosslinking but not contained in the Lyocell fiber;
[0089] Step S103: Detect the content difference of the characterizing element in the crosslinking agent before and after the Lyocell fiber is prepared, and obtain the crosslinking agent reaction amount through conversion;
[0090] Among them, the characterization elements of the cross-linking agent are tested using an organic element analyzer.
[0091] Wherein, in step S1, the method for detecting the change of fiber wet wear value over time comprises the following steps:
[0092] Step S201: Under set conditions, different detection moments are selected within a set time interval;
[0093] Step S202: at different detection times, respectively detecting the wet wear value of the fiber to be detected;
[0094] Step S203: With the detection time as the horizontal coordinate and the wet wear value of the tested fiber corresponding to the detection time as the vertical coordinate, the change of the fiber wet wear value over time is obtained.
[0095] In step S201, the set conditions include a temperature range of -20°C to 100°C and a humidity range of 0-100%.
[0096] Wherein, in step S1, the method for detecting the wet wear value and the coefficient of variation of the fiber after adding alkali and heating includes:
[0097] Step S301: The preliminarily prepared fiber to be tested is subjected to an alkali solution of a set concentration, and is heated at a set temperature for a set time to obtain the fiber to be tested after alkali addition and heating;
[0098] Step S302: After the fiber to be tested is washed and dried after adding alkali and heating, the wet wear value and coefficient of variation of the fiber after adding alkali and heating are calculated based on the washed and dried fiber to be tested and the initially prepared fiber to be tested.
[0099] Among them, in step S1, in the process of detecting the wet wear value and the coefficient of variation of the fiber to be tested after adding alkali and heating, the alkali solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate; the mass percentage of the solute in the alkali solution is 0.5%-5%; the amount of alkali solution is 5 times-100 times the mass of the fiber to be tested; the set temperature range of the alkali solution treatment is 0℃-100℃, and the set time range of the alkali solution heating treatment is 10s-60min; the drying temperature range of the fiber to be tested after adding alkali and heating is 50℃-100℃, and the drying time range is 30s-60min.
[0100] Wherein, in step S1, the method for detecting the halogen content on the fiber comprises the following steps:
[0101] Step S401: using a digestion solution to digest the fiber to be tested under a digestion condition to obtain the digested fiber to be tested;
[0102] Step S402: Detect the halogen content in the digested fiber to obtain the halogen content on the fiber.
[0103] Among them, in step S401, during the digestion step, the digestion solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, sulfuric acid, and nitric acid; the digestion temperature ranges from 90°C to 300°C, the digestion time ranges from 1h to 24h, the mass percentage of the solute in the digestion solution ranges from 0.1% to 10%, and the mass of the digestion solution used is 5-100 times the mass of the fiber to be tested.
[0104] Among them, in step S1, in the performance index of fiber pH changing with aging time, the method for detecting fiber pH includes the following steps:
[0105] Step S501: Put 1g-10g of the fiber to be tested into a container;
[0106] Step S502: adding desalted water equivalent to 5 to 15 times the mass of the fiber to be tested into the container, so that the fiber to be tested is fully in contact with the desalted water, and a mixture of the fiber to be tested and the desalted water is obtained;
[0107] Step S503: sealing the container, allowing the mixture of the fiber to be tested and the desalted water to stand at room temperature for 1-24 hours to obtain the fiber to be tested after standing;
[0108] Step S504: squeeze out excess water from the fiber to be tested after being placed, to obtain a sample of the fiber to be tested;
[0109] Step S505: Detection to obtain the pH of the sample to be tested.
[0110] Among them, in step S1, the shelf life is the time interval from the completion of the preparation of the fiber to be tested to the failure of the fiber to be tested, wherein the failure of the fiber to be tested is that the final wet wear number of the fiber to be tested is less than 200 times. At this time, the fiber to be tested no longer has anti-fibrillation performance, and the wet wear number is tested using the FZT 52019-2018 standard.
[0111] Wherein, in step S1, the calculation formulas of the Haller factors F1 and F2 of the fiber to be tested are respectively:
[0112] F1=-1.109+0.03992×FFk-0.06502×FDk+0.04634×FFn-0.04048×FDn+0.08936×NM+0.02748×SFk+0.025595KFk
[0113] F2=-7.070+0.02771×FFk+0.04335×FDk+0.02541×FFn+0.03885×FDn-0.01542×NM+0.2891×SFk+0.1640×KFk
[0114] In the formula,
[0115] FFk-dry breaking strength of the tested fiber after moisture conditioning (cN / tex),
[0116] FDk-dry breaking elongation of the tested fiber after moisture conditioning (%),
[0117] FFn-wet breaking strength of the fiber to be tested (cN / tex),
[0118] FDn-wet breaking elongation of the tested fiber (%),
[0119] NM-wet modulus of the tested fiber at 5% elongation (cN / tex / 5%),
[0120] SFk-Hook dry strength of the tested fiber after moisture conditioning (cN / tex),
[0121] KFk-knot strength of the tested fiber after moisture conditioning (cN / tex),
[0122] Parameters FFk, FDk, FFn, FDn, NM, SFk, KFk all adopt GB / T 14337-2008 standard.
[0123] Among them, the Haller factor F1 of the common type of Lyocell fiber to be tested is 2-3, and F2 is 2-8.
[0124] Wherein, in step S1, the fiber spinning performance includes one or more of the yarn strength, +140% cotton neps, and +200% cotton neps of the tested fiber sample after spinning.
[0125] Wherein, in step S1, the method for detecting the number of times of fiber anti-flapping comprises the following steps:
[0126] Step S601: taking 0.01g-1g of the fiber to be tested;
[0127] Step S602: adding deionized water equivalent to 100 to 1200 times the mass of the fiber to be tested to obtain a mixture of the fiber to be tested and the deionized water;
[0128] Step S603: placing a mixture of the fiber to be tested and deionized water in a test bag to obtain a test bag containing the sample to be tested;
[0129] Step S604: The test bag containing the sample to be tested is placed in a beating instrument for a beating test, wherein the beating frequency of the beating instrument is set to 5 times / s-20 times / s;
[0130] Step S605: the occurrence of fibrillation in more than 10% of the fibers in the sample to be tested is used as a detection termination indicator, and the corresponding number of flapping times at this time is used as the fiber anti-flapping times.
[0131] In step S605, the fibrillation of more than 10% of the fibers in the sample to be tested is used as the detection termination indicator, and the corresponding number of beatings at this time is used as the fiber anti-beating number. During this step, the sample to be tested is observed through an optical microscope.
[0132] Wherein, in step S1, the method for detecting the amount of fiber dust includes the following steps:
[0133] Step S701: Obtain all solutions in the cross-linking process of the fiber to be tested, wherein the cross-linking process refers to the entire process from applying the cross-linking additive to cleaning the fiber;
[0134] Step S702: filtering the solution to obtain filter residue;
[0135] Step S703: Dry the filter residue and weigh it to obtain the fiber dust amount.
[0136] Example
[0137] The cross-linked fibers prepared in the following examples were placed in a constant temperature and humidity chamber for aging, with an aging temperature of 40°C and an aging humidity of 80%. Sampling tests were performed every 7 days to test the number of wet abrasion times and the pH value of the fiber. The shelf life was also obtained under this condition. The anti-slapping frequency test set the flapping frequency to 7 times / s. The following process was used to test the pH value of the fiber: 1.0±0.1g of fiber was weighed and placed in a beaker, and then 10±1g of desalted water was weighed and poured into the beaker containing the fiber to allow the fiber to fully contact with water. The beaker was sealed with a sealing film and placed at room temperature for 24 hours. The fiber was taken out, and the excess water was squeezed out, and the pH value of the solution was tested.
[0138] Example 1
[0139] The low fibrillation fiber was prepared by the "fiber web cross-linking" process, and the cross-linking agent was 2,4-dichloro-6-hydroxy-1,3,5-triazine sodium salt (NHDT). The following process was used for alkali heating: 5.0±0.1g of low fibrillation fiber was prepared, 50±1g of NaOH solution was prepared, and the concentration was 1%, and it was heated to 80°C, and then the fiber was placed in the hot alkali for 1min, and the fiber was taken out and washed to neutrality, and placed in an 80°C oven for 5min. The following process was used for fiber digestion: 1.0±0.1g of low fibrillation fiber was placed in 100±10g of KOH solution with a concentration of 5%, and then poured into a digestion tube for digestion. The digestion temperature was 200°C and the digestion time was 8h.
[0140] Example 2
[0141] The low fibrillation fiber was prepared by the "fiber web cross-linking" process, and the cross-linking agent was 2,4-dichloro-6-hydroxy-1,3,5-triazine sodium salt (NHDT). The following process was used for alkali heating: 2.0±0.1g of low fibrillation fiber was prepared, 30±1g of Na2CO3 solution was prepared, and the concentration was 3%, and heated to 95°C, and then the fiber was placed in the alkali and heated for 15 minutes, and the fiber was taken out and washed to neutrality, and placed in a 100°C oven for 3 minutes. The following process was used for fiber digestion: 1.0±0.1g of low fibrillation fiber was placed in a 100±10gH2SO4 solution with a concentration of 2%, and then poured into a digestion tube for digestion. The digestion temperature was 180°C and the digestion time was 12h.
[0142] Example 3
[0143] The non-fibrillated fiber was prepared by the "fiber web cross-linking" process, and the cross-linking agent was 1,3,5-triacryloylhexahydro-1,3,5-triazine (TAHT). The following process was used for alkali heating: 1.0±0.1g of low fibrillated fiber was prepared with 10±1g of NaOH solution, the concentration of which was 0.5%, and heated to 80°C. Then the fiber was placed in the hot alkali for 1min, the fiber was taken out and washed to neutrality, and placed in an oven at 80°C for 5min.
[0144] Table 1
[0145]
[0146]
[0147] The results in Table 1 show that this evaluation system can completely distinguish cross-linked fibers made with different cross-linking agents, and the different application effects of different cross-linked fibers can be inferred based on the test results, so as to select the corresponding application fields. This evaluation system comprehensively and completely evaluates the performance of cross-linked fibers, and is not only applicable to NHDT and TAHT cross-linking agents, but also to other cross-linking agents.
[0148] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0149] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing Lyocell fiber, characterized in that: The following steps are involved: Performing performance evaluation on the prepared Lyocell fiber, the performance evaluation including: cross-linking performance evaluation, mechanical performance evaluation, long-cycle performance evaluation, and application performance evaluation, to obtain evaluation results; According to the evaluation results, Lyocell fibers that meet the evaluation standards are selected to obtain Lyocell fiber products.
2. The method for preparing Lyocell fiber according to claim 1, characterized in that: The cross-linking performance evaluation index includes one or more of the following: the reaction amount of the cross-linking agent, the change of the fiber wet wear value over time, the wet wear value and coefficient of variation of the fiber after adding alkali and heating, the halogen content on the fiber, and the number of times the fiber resists beating.
3. The method for preparing Lyocell fiber according to claim 1, characterized in that: The long-term performance evaluation indexes include the reaction degree of fiber pH, fiber wet abrasion value, and Halle factors F1 and F2 with aging time and / or shelf life.
4. The method for preparing Lyocell fiber according to claim 1, characterized in that: The mechanical property evaluation indexes include fiber Haller factors F1 and F2.
5. The method for preparing Lyocell fiber according to claim 1, characterized in that: The application performance evaluation index includes one or more of the fiber spinning performance, the fiber anti-beating times, and the fiber dust amount.
6. The method for preparing Lyocell fiber according to claim 2, characterized in that: The detection method of the cross-linking agent reaction amount comprises the following steps: Get the name of the crosslinking agent used in the preparation of Lyocell fibers; According to the name of the cross-linking agent, determine the characterizing element of the cross-linking agent, wherein the characterizing element of the cross-linking agent is an element contained in the cross-linking agent but not contained in the Lyocell fiber; Detecting the content difference of the characterizing element in the crosslinking agent before and after the Lyocell fiber is prepared, and obtaining the reaction amount of the crosslinking agent through conversion; Wherein, the characterizing elements of the cross-linking agent are tested by an organic element analyzer.
7. The method for preparing Lyocell fiber according to claim 2, characterized in that: The method for detecting the change of fiber wet wear value over time comprises the following steps: Under the set conditions, different detection moments are selected within the set time interval; At different testing moments, the wet wear value of the tested fiber is tested respectively; The detection time is taken as the horizontal coordinate, and the wet wear value of the fiber to be detected corresponding to the detection time is taken as the vertical coordinate, so as to obtain the change of the fiber wet wear value over time.
8. The method for preparing Lyocell fiber according to claim 7, characterized in that: The set conditions include a temperature range of -20°C to 100°C and a humidity range of 0-100%.
9. The method for preparing Lyocell fiber according to claim 2, characterized in that: The method for detecting the wet abrasion value and the coefficient of variation of the fiber after adding alkali and heating comprises: The preliminarily prepared fiber to be tested is subjected to an alkali solution of a set concentration, and is heated for a set time under a set temperature condition to obtain the fiber to be tested after adding alkali and heating; After the alkali-added and heated fiber to be tested is washed and dried, the wet wear value and coefficient of variation of the fiber after alkali-added and heated are detected and calculated based on the washed and dried fiber to be tested and the initially prepared fiber to be tested.
10. The method for preparing Lyocell fiber according to claim 9, characterized in that: During the step of detecting the wet abrasion value and coefficient of variation of the fiber to be tested after adding alkali and heating, The alkali solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate; In the alkali solution, the mass percentage of the solute is 0.5%-5%; The amount of lye used is 5 to 100 times the mass of the fiber to be tested; The set temperature range of alkali solution treatment is 0℃-100℃, and the set time range of alkali solution heating treatment is 10s-60min; The drying temperature of the tested fiber after adding alkali and heating is in the range of 50°C-100°C, and the drying time is in the range of 30s-60min; Preferably, the method for detecting the halogen content on the fiber comprises the following steps: Using a digestion solution under a digestion condition to digest the fiber to be tested, to obtain the digested fiber to be tested; Detecting the halogen content in the fiber to be tested after the digestion to obtain the halogen content on the fiber; Preferably, during the digestion step, The digestion solution is selected from one or more of ammonia water, sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, sulfuric acid, and nitric acid; The digestion temperature ranges from 90°C to 300°C, the digestion time ranges from 1h to 24h, the mass percentage of the solute in the digestion solution ranges from 0.1% to 10%, and the mass of the digestion solution used is 5 to 100 times the mass of the fiber to be tested; Preferably, in the performance index of fiber pH change with aging time, the method for detecting fiber pH comprises the following steps: Place 1g-10g of the fiber to be tested in a container; Adding desalted water in an amount of 5 to 15 times the mass of the fiber to be tested into the container, so that the fiber to be tested is fully in contact with the desalted water, to obtain a mixture of the fiber to be tested and the desalted water; The container is sealed, so that the mixture of the fiber to be tested and the desalted water is placed at room temperature for 1-24 hours to obtain the fiber to be tested after being placed; Squeeze out excess water from the fiber to be tested after being placed to obtain a sample of the fiber to be tested; Detecting to obtain the pH of the sample to be tested; Preferably, the shelf life is the time interval from the completion of the preparation of the fiber to be tested to the failure of the fiber to be tested, wherein the failure of the fiber to be tested is when the final wet wear number of the fiber to be tested is less than 200 times, at which point the fiber to be tested no longer has anti-fibrillation performance, and the wet wear number is tested using the FZT 52019-2018 standard; Preferably, the calculation formulas for the Haller factors F1 and F2 of the fiber to be tested are: F1=-1.109+0.03992×FFk-0.06502×FDk+0.04634×FFn-0.04048×FDn+0.08936×NM+0.02748×SFk+0.025595KFk F2=-7.070+0.02771×FFk+0.04335×FDk+0.02541×FFn+0.03885×FDn-0.01542×NM+0.2891×SFk+0.1640×KFk In the formula, FFk-dry breaking strength of the tested fiber after moisture conditioning (cN / tex), FDk-dry breaking elongation of the tested fiber after moisture conditioning (%), FFn-wet breaking strength of the fiber to be tested (cN / tex), FDn-wet breaking elongation of the tested fiber (%), NM-wet modulus of the tested fiber at 5% elongation (cN / tex / 5%), SFk-Hook dry strength of the tested fiber after moisture conditioning (cN / tex), KFk-knot strength of the tested fiber after moisture conditioning (cN / tex), Parameters FFk, FDk, FFn, FDn, NM, SFk, KFk all adopt GB / T 14337-2008 standard. Among them, the Holler factors F1 and F2 of the common type of Lyocell fibers to be tested are 2-3 and 2-8 respectively; Preferably, the fiber spinning performance includes one or more of the yarn strength, +140% cotton neps, and +200% cotton neps of the tested fiber sample after spinning; Preferably, the method for detecting the fiber anti-flapping times comprises the following steps: Take 0.01g-1g of the fiber to be tested; Adding deionized water in an amount equivalent to 100 to 1200 times the mass of the fiber to be tested to the fiber to be tested, to obtain a mixture of the fiber to be tested and the deionized water; Placing a mixture of the fiber to be tested and deionized water in a test bag to obtain a test bag containing the sample to be tested; The test bag containing the sample to be tested is subjected to a beating test in a beating instrument, wherein the beating frequency of the beating instrument is set to 5 times / s-20 times / s; The occurrence of fibrillation in more than 10% of the fibers in the sample to be tested is taken as the detection termination index, and the corresponding number of beatings at this time is taken as the number of fiber anti-beating; Preferably, during the step of taking the occurrence of fibrillation of more than 10% of the fibers in the sample to be tested as the detection termination index and taking the corresponding number of flapping times as the number of anti-flapping times of the fibers, the observation of the sample to be tested is performed by an optical microscope; Preferably, the method for detecting the amount of fiber dust comprises the following steps: Obtaining all solutions in the cross-linking process of the fiber to be tested, wherein the cross-linking process refers to the entire process from applying the cross-linking additive to cleaning the fiber; filtering the solution to obtain a filter residue; The filter residue is dried and weighed to obtain the fiber dust amount.